-5x-4(-x-17)=76

Simple and best practice solution for -5x-4(-x-17)=76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-4(-x-17)=76 equation:


Simplifying
-5x + -4(-1x + -17) = 76

Reorder the terms:
-5x + -4(-17 + -1x) = 76
-5x + (-17 * -4 + -1x * -4) = 76
-5x + (68 + 4x) = 76

Reorder the terms:
68 + -5x + 4x = 76

Combine like terms: -5x + 4x = -1x
68 + -1x = 76

Solving
68 + -1x = 76

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-68' to each side of the equation.
68 + -68 + -1x = 76 + -68

Combine like terms: 68 + -68 = 0
0 + -1x = 76 + -68
-1x = 76 + -68

Combine like terms: 76 + -68 = 8
-1x = 8

Divide each side by '-1'.
x = -8

Simplifying
x = -8

See similar equations:

| y+7=7(x-2) | | -10(b+645)=-490 | | 15-1/2b= | | 4w-60=440 | | 2g-17=1 | | y-6=6(x+6) | | 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 | | 10x+3+3x+24=180 | | 24x^2+-12x+-12=0 | | 22/25-7/10 | | 5/20=30/x | | 8x-1+15x+3x+9=90 | | y+4=4(x+7) | | -7y-7=-5(y+5) | | Log(4x+12)=2 | | 72x+56=-84-37x | | 3u-5=10 | | 5/20=3-/x | | 8x-1+15x+3x+9=180 | | 8x-6y=56 | | Q/6--112=125 | | 0=-16x^2+560 | | -9/p-3=3/5 | | 12=-7v+5(v+6) | | y+7=4(x-9) | | 20+-6n=-12+-2n | | 2w+30=460 | | cos(0.5)x=-1 |

Equations solver categories